Two remarkable new species of the Australian moth genus Gallaba Walker (Lepidoptera: Notodontidae, Notodontinae) from the highlands of Tasmania - Mcquillan, Peter B.; Chen, Jingyi; Fountain-Jones, Nicholas M. (Zootaxa, 2024)
The distinctive notodontine moth genus Gallaba Walker, 1865 is confined to eastern and southern Australia where multiple species inhabit forests, woodlands and heathlands from sea level to montane forests of at least 1650m. The continental island of Tasmania supports four Gallaba species (including these two new endemics) at the current global southern limit of Notodontidae. Two distinctive new species are described from montane and subalpine Tasmania: Gallaba constellata sp. nov. and Gallaba kirkpatricki sp. nov. Both exhibit distinctive phenotypes including extraordinarily long rami in the male antennae, but their phylogenetic relationships to the rest of the genus must await a full revision of Gallaba and allied genera. We find no evidence for earlier claims that G. duplicata Walker, 1865 occurs in Tasmania. It was likely confused with the phenotypically similar Hobartina amblyiodes (Turner, 1931) and we remove it from the Tasmanian checklist. Biological information about Gallaba is very limited, but we have discovered that the larva of Gallaba kirkpatricki sp. nov. feeds on the pandaniform tall shrub Richea pandanifolia (Ericaceae: Epacridoideae). The Ericaceae is a novel hostplant family for Australian Notodontinae, although it is sparingly used by notodontines in tropical Asia. The mesic habitat and foodplants of these species are vulnerable to fire risk in montane areas which has been increasing rapidly in frequency and extent in recent years due to drying of the environment caused by climate change.